(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
Cervantes throughout his literary production confronts diverse doctrines of ratio philosophica on death and transcendence. Among them we should emphasize the mortalist thesis, or neo-Aristotelian thnetopsychism, of the School of Padua, whose main exponent was Pedro Pomponazzi. In this article we will focus on the presence of this doctrine in his eight comedies of 1615.